Discussion of Extinction-Based Behavioral Sleep Interventions for Young Children and Reasons Why Parents May Find Them Difficult - Etherton, H.; Blunden, S.; Hauck, Yvonne (2016)
The majority of behavioral sleep interventions for young children involve extinction procedures where parents must ignore their child's cries for a period. Many parents have difficulties with this, contributing to attrition, non-compliance, and treatment avoidance. Yet why these methods are difficult to implement has rarely been addressed in the literature. This paper discusses seven potential reasons why parents may find extinction sleep interventions difficult: enduring crying, practical considerations, fear of repercussions, misinformation, incongruence with personal beliefs, different cultural practices, and parent wellness. These reasons are discussed in relation to the current literature. Practicing health professionals and sleep researchers could benefit from an awareness of these issues when suggesting extinction interventions and offering alternatives which may be more appropriate for family circumstances and facilitate parental informed choice.